Antimicrobial activity of Myrtus communis L. and Origanum syriacum L. against some of human pathogenic bacteria - زينب, اسمهان; عيسى, عفيفة (Latakia University Journal -Biological Sciences Series, 2020)
In the present study, essential oils taken from the leaves of Myrtus communis L., Origanum syriacum L., growing in mountain Al-Basset forests, were obtained by steam distillation method, the antibacterial activities of the essential oils were also determined on 13 pathogenic microorganisms (seven isolates Gram-negative, five isolates Gram positive bacteria and one fungi of Candid albicans, were obtained from laboratory of Tishreen hospital) tested using the agar well diffusion method. The results showed that the oil from leaves of Myrtus communis L. and Origanum syriacum L. has antibacterial activities against most isolated pathogenic Gram positive and Gram negative bacteria also against Candid albicans. These activities were better than of all antibiotics that were used as control at high concentrations (25-30) mg/disc, Depending on these results, it can be concluded that essential oils taken from the leaves of Myrtus communis L. and Origanum syriacum L. have high antibacterial activities against broad spectrum of pathogenic microorganisms, Gram-negative and Gram positive bacteria, also against Candid albicans.